IoT-Based Guppy Aquaculture Monitoring System Using C 4.5 Method on Thingspeak Platform - abidin, aa zezen zaenal; Murdianingsih, Yuli; Ruhiyat, Ilham; Suryadi, Usep Tatang; Iskandar Othman, Mohd. Fairuz; Faizal, Muhammad (International Journal of Artificial Intelligence Research, 2022)
Monitoring water media in Guppy fish farming is a major problem that must be solved. monitoring is carried out to obtain a decision whether the media is suitable or not suitable for getting good guppy fish.This study aims to extract knowledge in order to make decisions on the quality of Guppy fish water media through data obtained from the IoT system.The main contribution of this research is the effort to obtain new knowledge from data collected through IoT systems. New knowledge is obtained from water quality parameter data acquired by sensors of temperature, water level and pH. data from the sensor is sent to the Thingspeak cloud application via the microcontroller module. Data from the cloud is extracted into new knowledge in the form of decision-making rules for the quality of Guppy fish water media. To validate the method used, an analysis was performed using a confusion matrix in the rapidminer application. tested for the C 4.5 method and the Naive Bayes methodThe results obtained the same high accuracy of 100 percent. It is possible that this IoT system can be applied in a larger scope, for example monitoring the aquariums of various Guppy fish farming communities in a city, so that real time data on the quality of Guppy fish is obtained within the scope of Smart City.